Palm oil clinker as partial coarse aggregate replacement in producing high flexural holllow section beam - Sujendran , Thangarjoo (2014)
Concrete is a most widely used material in the construction line. There were many modifications made in the concrete materials. The lightweight aggregate concrete containing palm oil clinkers were introduced as a method to reduce the amount of gravel aggregates in order to produce concrete with sufficient strength. The palm oil clinker was used as the coarse and fine aggregate replacement. Hollow section beam with palm oil clinker as a partial coarse aggregate replacement was introduced. Concrete can withstand compression force but weak in resisting the tensile force. Therefore, we reduce the consumption of concrete at the tensile region. Thus after we reduce the concrete at the tensile region it is called a hollow section beam. The objective of the study is to determine the ultimate strength and deflection of the hollow section beam and also to determine the effect of cavity size in the hollow section beams. Three beams with cavity size 100mm x 40mm, lOOmm x SOmm and 100mmx 60mm were produced. The cross sectional area of the hollow beam is 250mm x 300mm with a length of 2000mm. In order to construct the beam, searching and collecting information regarding hollow section beam and palm oil clinker were carried out. The palm oil clinker was crushed into the form of coarse aggregate in the preparation of the raw material. Besides that, the formwork and reinforcement steelwork were carried out. The flexural tests for the beam were conducted by using Magnus Frame. The graph load against deflection, load against time, deflection against time and the bar chart for loaddeflection ratio was analysed. The beam with hollow cavity 100mmx60mm gives the best result. The beam able to withstand the highest ultimate load which is 145.55kN and with a deflection of 25.72mm which is lowest. The loaddeflection ratio of the hollow beam of 100mm x 60mm has the highest load- deflection ratio which is 5.67kN/mm. This means 5.67kN of load is required to produce 1mm deflection. In conclusion the results obtained from the research fulfill the objective of the study. The ultimate strength of the palm oil clinker as a partial coarse aggregate replacement in hollow section beam is 145.55kN with a deflection of 25.72mm. Besides that, 100mm x 60mm is the largest cavity size among the three beams. Thus, it fulfills the criteria as saving more concrete materials and having the lowest self weight.